PENGARUH KOMPETENSI AUDITOR, SKEPTISISME PROFESIONAL, KOMPLEKSITAS TUGAS, DAN SELF-EFFICACY TERHADAP AUDIT JUDGEMENT (STUDI PADA KAP DI WILAYAH KOTA JAKARTA) - Azzahra Aliyya Arnas; Emrinaldi Nur DP; Lila Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2026)
This study examines the influence of auditor competence, professional skepticism,task complexity, and self-efficacy on audit judgement in Public Accounting Firmsin Jakarta. This quantitative research employed a survey method involving 60auditors selected using purposive sampling. Data were analyzed using StructuralEquation Modeling (SEM) with SmartPLS 4. The results indicate that auditorcompetence and professional skepticism have a significant positive effect on auditjudgement, while task complexity and self-efficacy do not significantly affect auditjudgement. The model explains 42.7% of the variance in audit judgement. Thisstudy contributes to auditing literature and provides practical implications forimproving audit quality. Keyword: audit judgement; auditor competence; professional skepticism; selfefficacy; task complexity